Pemetaan Data Siswa Berprestasi Pada SMA Nurul Iman Palembang - Lambardo, Fakhri; Purnama, Andhika (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2024)
Student learning achievement is very important because learning achievement is one of the illustrations of the level of success of activities during the lesson. One of the goals in the learning process is to achieve an achievement in learning. Learning achievement is the learning result obtained by students after following the teaching and learning process carried out by the teacher. The role of parents is very important in guiding their children in motivating them to study hard. In order for their learning achievement to be good, parents need to devote all their guidance to their children. The Principal of Nurul Iman Senior High School (SMA) Palembang said that Nurul Iman Senior High School has approximately 300 science and social science students from grades 1 to 3. Each student has their own abilities in the way they receive the knowledge they get at school and there are many students who excel as seen from students whose UAS scores, Extracurricular, Attitude Scores, Attendance. Some show that parents with sufficient educational backgrounds are very concerned about their children's education, but in other conditions parents are indifferent or even do not know the problems of their children's education, especially at Nurul Iman Senior High School Palembang. The diversity of backgrounds and parental attention is a separate problem for children, especially the role of parents in guiding children during the educational process at SMA Nurul Iman Palembang. The problem that often arises at SMA Nurul Iman is that many still prioritize productive subject competencies over adaptive and normative subjects. Many SMA Nurul Iman students are good at producing work according to their competencies but they are weak in adaptive and normative subjects. For example, there are many extracurricular students but they are weak in Mathematics which is one of the requirements for graduation. Therefore, attention is needed by educational units to be able to organize learning that can overcome this problem.